Analysis of Understanding the Concept of Environmental Pollution for Middle School and High School Students using a Cross-Sectional Approach - Rifaul Annisa; Nuryani Rustaman; Lilit Rusyati; Taufik Rahman (Scientiae Educatia: Jurnal Pendidikan Sains, 2025)
Environmental pollution is a concept-based science learning material related to life and the environment. Students' conceptual understanding of environmental pollution is very low because they often memorize without understanding the deeper meanings of the concepts they study. This study aims to analyze the conceptual understanding of tenth-grade high school students and seventh-grade junior high school students regarding environmental pollution. The method used in this study was a cross-sectional survey comprising the preparation stage of creating an online questionnaire with 4 questions, the implementation stage of sending the questionnaire, and the data analysis stage of student responses. Based on the data analysis, some tenth-grade high school students and seventh-grade junior high school students still have limited conceptual understanding because they focus on textbook concepts without understanding their meanings and relationships to environmental issues. However, some high school students already have a broad conceptual understanding. This indicates that the higher the level of education, the more important concepts emerge. The problems faced by junior high school students and some high school students can be overcome by choosing a learning strategy based on direct environmental practice so that students not only understand the concepts but also develop a sense of concern for the environment.